Through Hermopolitan lenses : studies on the so-called Book of Two Ways in ancient Egypt - Sherbiny, Wael. (Probleme der Ägyptologie, 2017)
The so-called Book of Two Ways is a long and complex composition containing both texts and images. It reached us on the insides of some coffins and tomb walls, principally from the Hermopolitan nome in the Egyptian Middle Kingdom (2055-1650 BC). Wael Sherbiny presents a pioneering study based on all the original and hitherto unpublished sources. Through Hermopolitan Lenses challenges many of the traditional views related to this composition as part of the Coffin Texts. It also provides an integrated pictorial and textual analysis revealing many unprecedented facts. The oldest and longest leather manuscript from ancient Egypt (the Cairo leather roll), which Sherbiny rediscovered during his study and soon became world news, features here for the first time as well.